Ixabepilone‐induced mitochondria and sensory axon loss in breast cancer patients. (2nd September 2014) - Ebenezer, Gigi J.; Carlson, Karen; Donovan, Diana; Cobham, Marta; Chuang, Ellen; Moore, Anne; Cigler, Tessa; Ward, Maureen; Lane, Maureen E.; Ramnarain, Anita; Vahdat, Linda T.; Polydefkis, Michael
Abstract Background We sought to define the clinical and ultrastructure effects of ixabepilone (Ix), a microtubule‐stabilizing chemotherapy agent on cutaneous sensory nerves and to investigate a potential mitochondrial toxicity mechanism. Methods Ten breast cancer patients receiving Ix underwent total neuropathy score clinical (TNSc) assessment, distal leg skin biopsies at cycle (Cy) 3 (80–90 mg/m2), Cy5 (160–190 mg/m2), and Cy7 (>200 mg/m2) and were compared to 5 controls. Skin blocks were processed for EM and ultrastructural morphometry of Remak axons done. Results At baseline, Ix‐treated subjects had higher TNSc values (4.5 ± 0.8 vs. 0.0 ± 0.0), greater percentage of empty (denervated) Schwann cells (29% vs. 12%), altered axonal diameter (422.9 ± 17 vs. 354.9 ± 14.8 nm, P = 0.01), and axon profiles without mitochondria tended to increase compared to control subjects (71% vs. 70%). With increasing cumulative Ix exposure, an increase in TNSc values (Cy3: 5.4 ± 1.2, Cy7: 10 ± 4, P < 0.001), empty Schwann cells (39% by Cy7), and dilated axons (in nm, Cy3: 506.3 ± 22.1, Cy5: 534.8 ± 33, Cy7: 527.8 ± 24.4; P < 0.001) was observed. In addition, axon profiles without mitochondria (Cy3:74%, Cy7:78%) and mitochondria with abnormal morphology (grade 3 or 4) increased from 24% to 79%. Schwann cells with atypical mitochondria and perineuronal macrophage infiltration in dermis were noted. Interpretation This study provides functional and structural evidence that Ix exposure induces a dose‐dependent toxicity on small sensory fibers with an increase in TNSc scores and progressive axonal loss. Mitochondria appear to bear the cumulative toxic effect and chemotherapy‐induced toxicity can be monitored through serial skin biopsy‐based analysis.